Aluminized Energetic Coordination Polymers Constructed from Transition Metal Centers (Co, Ni, and Cu). Issue 10 (6th July 2021) - Ma, Xiaoxia; Chen, Xi; Li, Yuxiang; Qiao, Zhiqiang; Yang, Guangcheng; Zhang, Kaili
Abstract: The afterburning effect of aluminized explosives makes them have strong damage ability to soft targets, but the aluminum particles in the composition often cannot achieve proper combustion. The high ignition temperature of micron aluminum powder is one of the main reasons. In this work, we introduce nanothermite reaction with low onset temperature (<660 °C) into aluminized explosives by replacing the base explosives with energetic coordination polymers (ECPs). The decomposition products of many ECPs contain corresponding metal oxides that will react with aluminum via thermite reaction. Three kinds of ECPs ([CoC2 H4 N8 O4 ]n, [NiC2 H4 N8 O4 ]n and [CuC2 H4 N8 O4 ]n ) are constructed and compounded with nano‐aluminum (nano‐Al) particles to form aluminized ECPs. The influence of metal ion species and Al/Metal (Al/Me) molar ratio on their energetic properties are systematically studied. The results show that the exothermic thermite reaction with low onset temperature plays an important role in the combustion propagation of aluminized ECPs, and the possible mechanism is proposed. When the Al/Me molar ratio is 3–4, the aluminized ECPs have the best peak pressure and pressurization rate. At the optimum molar ratio, the pressure and pressurization rate of aluminized ECP(Co) are much higher than those of aluminized ECP(Ni) and ECP(Cu). Among the three kinds of aluminized ECPs, the aluminized ECP(Co) has the best energetic characteristics and can be used as a preferred choice. However, for the applications that require a long‐time heat supply, aluminized ECP(Cu) will be suitable. Abstract :